A matching approach to business services and software services. (2018) - Zhao, Junfeng; Zhou, Jiantao; Yang, Hongji
Recent studies have shown that service-oriented architecture (SOA) has the potential to revive enterprise legacy systems (Cai et al., 2011; Gaševic and Hatala, 2010; De Castro et al., 2011; Chengjun, 2008; Elgedawy, 2009; Tian et al., 2007; Chen et al., 2009; Zhang et al., 2006; Sindhgatta and Ponnalagu, 2008; Khadka, 2011), making their continued service in the corporate world viable. In the process of reengineering legacy systems to service-oriented architecture, some software services extracted in legacy systems can be reused to implement business services in target systems. In order to achieve efficient reuse to software services, a matching approach is proposed to extract the software services related to specified business services, where service semantics and structure similarity measures are integrated to evaluate the similarity degree between business service and software services. Experiments indicate that the approach can efficiently map business services to relevant software services, and then legacy systems can be reused as much as possible.